2017
DOI: 10.1093/bioinformatics/btx216
|View full text |Cite
|
Sign up to set email alerts
|

ClusPro PeptiDock: efficient global docking of peptide recognition motifs using FFT

Abstract: SummaryWe present an approach for the efficient docking of peptide motifs to their free receptor structures. Using a motif based search, we can retrieve structural fragments from the Protein Data Bank (PDB) that are very similar to the peptide’s final, bound conformation. We use a Fast Fourier Transform (FFT) based docking method to quickly perform global rigid body docking of these fragments to the receptor. According to CAPRI peptide docking criteria, an acceptable conformation can often be found among the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 22 publications
0
96
0
Order By: Relevance
“…Step A | Generation of fragment set to represent the peptide conformer ensemble: In a previous study we have shown that the bound peptide conformation can be well represented by extraction of short fragments from the PDB based on information of known binding sequence motifs 24 . Here we have generalized this approach beyond motifs, using fragment libraries selected by the Rosetta fragment picker protocol 22 based on sequence and secondary structure similarity (see Methods ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Step A | Generation of fragment set to represent the peptide conformer ensemble: In a previous study we have shown that the bound peptide conformation can be well represented by extraction of short fragments from the PDB based on information of known binding sequence motifs 24 . Here we have generalized this approach beyond motifs, using fragment libraries selected by the Rosetta fragment picker protocol 22 based on sequence and secondary structure similarity (see Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by our recent advance in global peptide docking using a motif-focused approach 24 we ventured into the development of a more generalized protocol. We initially calibrated our docking approach on a small representative set of nine peptide– protein complexes (highlighted in bold in Table 1 ; see also Supplementary Table S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 hydrogen bonds (Table S4) and 1 salt bridge hold the complex together. We use PIPER-Flex PEP dock (32)(33)(34) to see the interactions between first 15 amino acids of N-terminal region of PduB' with D subunit of the enzyme (Fig. 6).…”
Section: Predicting Residue Level Interactions Between Pdubb' and Pducdementioning
confidence: 99%